Performance Study of Unbalanced Load on Delta Transformer - Pelpinus Sinay (International Journal Multidisciplinary Science, 2026)
A transformer is a device that can transfer (channel) and convert electrical energy from one circuit to another at the same frequency based on the principle of electromagnetic induction. The transformer to be used in this study is a three-phase delta connection transformer, which can be used to transmit three-phase electrical power to the load, which is connected to the delta-connected load. The performance of the unbalanced load on the open delta transformer, when loaded with an unbalanced load that is not the same size in each phase, causes an increase in current in each phase, so that there is an increase in input power absorbed by the unbalanced load resulting in greater power losses (loses) with reduced efficiency. The purpose of the study is to study the performance of unbalanced loads in delta transformers and The research method is an experimental method in the laboratory, which includes testing on three-phase transformers of delta connection in an unbalanced load state. The measurement results showed that there was a difference in the performance (yield of the discharge) effect of the unbalanced load between the average current with the loss and with the efficiency of the delta transformer.